2012
DOI: 10.1142/s0192415x12500425
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Schisandrin B Against Cyclosporine A-Induced NephrotoxicityIn VitroandIn Vivo

Abstract: Schisandrin B (Sch B) is an active ingredient of the fruit of Schisandra chinensis. It has many therapeutic effects arising from its tonic, sedative, antitussive and antiaging activities and is also used in the treatment of viral and chemical hepatitis. The aim of this study was to investigate the protective effects of Sch B on cyclosporine A (CsA)-induced nephrotoxicity in mice and HK-2 cells (a human proximal tubular epithelial cell line). After gavage with Sch B (20 mg/kg) or olive oil (vehicle), mice recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The salt-depleted rats underwent renal injury faster than rats on normal salt diet, and their kidneys showed morphological and pathological changes similar to those occurring in renal transplant patients. 42 In agreement with previous studies, 43 45 the present investigation revealed that administration of CsA results in deterioration of renal function as evidence by the marked elevation of serum urea and Cr levels. Furthermore, the development of CsA-induced renal dysfunction in the current investigation was accompanied by a rise in renal MDA levels along with a significant reduction in renal CAT activity and GSH-Px levels.…”
Section: Discussionsupporting
confidence: 93%
“…The salt-depleted rats underwent renal injury faster than rats on normal salt diet, and their kidneys showed morphological and pathological changes similar to those occurring in renal transplant patients. 42 In agreement with previous studies, 43 45 the present investigation revealed that administration of CsA results in deterioration of renal function as evidence by the marked elevation of serum urea and Cr levels. Furthermore, the development of CsA-induced renal dysfunction in the current investigation was accompanied by a rise in renal MDA levels along with a significant reduction in renal CAT activity and GSH-Px levels.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, these promising results are to be related to a potential reduction in the loss of tubular cells in vivo, what could reduce tubular atrophy and AKI. This has notably been demonstrated for Schi B in a cyclosporine A-mediated nephrotoxicity model (Zhu et al, 2012).…”
Section: Prevention Of Cell Death Via Apoptosismentioning
confidence: 77%
“…1 (Panossian and Wikman, 2008). These compounds have been involved in recent in vivo and in vitro pharmacological studies, suggesting a protective effect in various pathological models (Jeong et al, 2012;Lee et al, 2012), with some studies focusing on nephrotoxicity (Park et al, 2012;Sohn et al, 2009aSohn et al, ,2009bStacchiotti et al, 2011;Zhu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Schizandrin B was shown to increase the intracellular ATP levels and to protect against Gentamicin and Cyclosporine A-induced nephrotoxicity by decreasing oxidative stress and cell death in vitro and in vivo (Chiu et al, 2008; Zhu et al, 2012). R. rosea extract activated the synthesis or resynthesis of ATP in skeletal muscles mitochondria and stimulated reparative energy processes after intense exercise in rats.…”
Section: Discussionmentioning
confidence: 99%